2019
DOI: 10.1088/1361-6560/ab0aa0
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of out-of-field surface doses due to the electron streaming effect in orthogonal magnetic fields

Abstract: The out-of-field surface dose contribution due to backscattered or ejected electrons, focused by the magnetic field, is evaluated in this work. This electron streaming effect (ESE) can contribute to out-of-field skin doses in orthogonal magnetic resonance guided radiation therapy machines. Using the EGSnrc Monte Carlo package, a phantom is set-up along the central axis of an incident 10 10 cm2 7 MV FFF photon beam. The phantom exit or entry surface is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 24 publications
(31 reference statements)
5
61
0
4
Order By: Relevance
“…This finding was subsequently confirmed by Malkov et al using the EGSnrc Monte Carlo simulations (17). Furthermore, Malkov et al implemented Monte Carlo simulations to study the ESE induced out-of-field surface dose enhancement with oblique phantom under various magnetic field strength, and they found that ESE can produce doses as high as 39.0 ± 0.2% of the maximum deliverable dose by the photon beam (18). An et al calculated and measured the air-electron stream doses outside the treatment field with ViewRay system by utilizing a custom-made acrylic phantom (19).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This finding was subsequently confirmed by Malkov et al using the EGSnrc Monte Carlo simulations (17). Furthermore, Malkov et al implemented Monte Carlo simulations to study the ESE induced out-of-field surface dose enhancement with oblique phantom under various magnetic field strength, and they found that ESE can produce doses as high as 39.0 ± 0.2% of the maximum deliverable dose by the photon beam (18). An et al calculated and measured the air-electron stream doses outside the treatment field with ViewRay system by utilizing a custom-made acrylic phantom (19).…”
Section: Introductionmentioning
confidence: 77%
“…All the dose calculations were performed with "dose-to-medium" mode by using Monaco's GPU based Monte Carlo platform GPUMCD (15), with a statistical uncertainty of 1% per control point and a dose grid resolution of 0.1 cm. According to previous studies, ESE mainly affects the out-offield in-air dose distribution in CC direction (18)(19)(20)(21). For esophageal cancer case, due to the proximity to target, out-offield neck and chin skin are most likely to be influenced by ESE.…”
Section: Treatment Planning and Evaluationmentioning
confidence: 96%
“…This was first observed and evaluated by Park et al (64), who, in the context of accelerated PBI delivered on the 0.35 T 60 Co ViewRay system, observed an electron stream in air extending toward the head and ipsilateral arm. This ESE is caused by electrons generated inside the body that, instead of scattering in random directions when leaving the body, start spiraling along the magnetic field (65). If unobstructed, this electron stream would reach the chin and arm, causing unwanted irradiation of the skin in these areas.…”
Section: Electron Stream Effectmentioning
confidence: 99%
“…Depending on the location of the high-dose region in the breast, this electron stream can also be directed toward the feet (Figure 4). Studies on phantoms and early clinical experiences suggest that the treatment planning system is able to fully describe the ESE and that the use of bolus material to shield the body parts located in the electron stream showed effective reduction of the dose in these regions (64)(65)(66).…”
Section: Electron Stream Effectmentioning
confidence: 99%
“…The union of a linear accelerator and an MRI in a single device to facilitate online adaptive MR guided radiotherapy was complex and required almost 20 years from an idea to a clinically available system [1]. The reasons for this were manifold: Unlike with cone-beam CT guided radiotherapy; the magnetic field of an MR-linac is permanent and impacts the dose distribution [2]. In addition, the moving linear accelator influences the magnetic field.…”
mentioning
confidence: 99%